Photometric CIELAB Analysis of the Gingiva: A Novel Approach to Assess Response to Periodontal Therapy - Mayer, Yaniv; Ginesin, Ofir; Machtei, Eli E. (Journal of periodontology (1970), 2017)
Background: A new photometric method is introduced for assessment of gingival condition and changes after periodontal therapy. Methods: Clinical data (probing depth [PD], plaque index [PI], gingival index [GI], bleeding on probing [BOP], and clinical attachment level) and photographs from 53 participants (26 males and 27 females) undergoing initial periodontal treatment were used for this analysis. Each maxillary anterior area was photographed before and 3 months after treatment. Digital image analysis was performed around one incisional tooth, and color data were expressed in terms of L*, a*, and b* values in accordance with the CIELAB color space. Non‐parametric Mann–Whitney U test was used for within‐group comparisons of disease resolution, as well as means and standard deviations of clinical parameters and ΔL, Δa, and Δb values from baseline to re‐evaluation. Results: Significant reduction in mean PI, GI, PD, and BOP were found after treatment in all groups (P <0.001). Significant differences (P <0.05) were recorded by diagnosis of chronic periodontitis in the a* coordinate when comparing treatment results with the baseline (P <0.004). Conclusion: Results of this study suggest potential benefit in using photometric analysis to assess gingival changes after therapy.